Demographic crisis as a threat to the national security of the Russian Federation - E. V. Yakutovich (Vestnik MGIMO-Universiteta)
The analysis of the demographic situation in the country, the ability of national threats in a negative population growth is considered a causal relationship crisis, including, possible projections of population change of the geopolitical picture of the world.